Pengembangan Model Ketahanan Sosial Masyarakat terhadap Dampak Media Massa Melalui Pemberdayaan PKK sebagai Agen Media Literacy di Kabupaten Banyumas - Shinta Prastyanti; Mite Setiansah; Sri Pangestuti (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2013)
The media exposure brought by many mass media today could not be stopped it again. Therefore media literacy education must be done soon. In the long term, media literacy education is hoped could realize social society tenacity particularly in facing social change caused by mass media. In the short term, media literacy education which is involved the member of PKK could realize media literacy society which is initiated by the smallest part of society, that is family. The research which is located in the District of Banyumas was done by using qualitative methods. The first year of research result shows that PKK cadre has had enough early knowledge about the kind of media with its positive and negative content although their knowledge is however limited on explicit content. Generally they also are as heavy viewer. Easily, availability, and informative content become the reason to access media. Most of PKK cadre in the District of Banyumas doing setting and monitoring as an effort to control the media impact particularly in their family. But they face a major problem which is limitation of information technology mastery and also the difference of taste and needs of their family.